Optimization of Pulsation Rate of the Milking System for the Mammary Gland Remodeling during Involution in Thai Crossbred Holstein Cows - A. Tiantong; K. Sasiwimonrit; S. Saengwong; W. Inyawilert; A. Chaokaur; S. E. Chen (Tropical Animal Science Journal, 2021)
This study aimed to investigate the effects of pulsation rate of the milking machine on the proteinous components and gelatinase activity in the mammary secretion for optimal tissue remodeling during the dry period in tropical dairy cows. Nine healthy primiparous Thai crossbred Holstein cows (75%HF) were milked with various pulsation rates (50, 60, and 70 cycles/min) one week after calving. The total protein contents of the secretions increased along the time course in 50 and 60 cycles/min groups but not in 70 cycles/min group and were not different among the 3 groups along the time course. Lactoferrin and BSA abundance of the 3 groups as well as γ-globulin in 50 and 70 cycles/min groups also increased in a time-dependent manner, in which only γ-globulin abundance in 60 cycles/min group 14 days before drying off and lactoferrin in 50 cycles/min group 14 days after drying off were significantly higher than those of the other 2 groups. In tissue remodeling by gelatinase activity analysis, 50 cycles/min group showed dramatic increases of Matrix metalloproteinase-9 (MMP-9) and MMP-2 activities after drying off, whereas 60 and 70 cycles/min groups had a significant but a smaller change (p<0.05) along the time course. Cows with 60 cycles/min exhibited dramatic increases of MMP-9 and MMP-2 activities than the other groups before drying off (p<0.05). The findings suggested that milking pulsation rate at 60 cycles/min resulted in higher activity of remodeling during mammary involution and thus may benefit the renewal and health of the udder in the long run.